if the first one is x, the second one is x/2, and the third one is x/2 also
so:
x + x/2 + x/2 = 64
2x = 64
x = 32
so the first fish is 32 ounces, and both the second and third are 16
2007-01-14 04:30:13
·
answer #1
·
answered by car of boat 4
·
1⤊
1⤋
No, your answer is incorrect, By the question, the weight of the third fish is the same as that of the second and your answer does not give that.OR try to verify your answers to see if these satisfy the other requirements of the problem.They don't.
Let the weights of the three fish be: second = x, First =2x and Third = x. Then x+2x+x=64
or 4x = 64 which leads to x = 16.
Hence, the weights of the three fish are respectively:
First=32 ounces, Second + 16 ounces and Third + 16 ounces.
2007-01-14 12:47:58
·
answer #2
·
answered by Anonymous
·
0⤊
0⤋
This would be easier if I could see you and explain, but I will try. The question is a bit misleading. The 1st is 2x the second. The third is 1/2 the first. This means that the 2nd and the 3rd are the same, and the first i 2x each. So I divided the whole number by 2, that equaled 32. now that I have the weight of the first fish, 32oz., I know that the other 2 are 1/2 of it, equaling 16 oz. each. The equation is is easy on paper but not as easy for me on the computer. Think about the question and you will see it easier.
2007-01-14 12:34:29
·
answer #3
·
answered by Joseph L 4
·
0⤊
0⤋
first fish was 32 ounces
second fish was 16 ounces
third fish 16 ounces
2007-01-14 12:34:18
·
answer #4
·
answered by cparkmi331 3
·
0⤊
0⤋
okay, let fish number two = x
therefore, fish number 1 = 2x (twice as big as the 2nd one)
and the 3rd fish, being half as large as the first, must be half of 2x, which is x.
the total weight is 64 ounces.
therefore 2x(first fish) + x(second fish) + x(third fish) = 64 ounces
2x + x + x = 64
4x = 64
x = 18
fish number one = 2x = 36 ounces
fish number two = x = 18 ounces
fish number three = x = 18 ounces
2007-01-14 12:35:53
·
answer #5
·
answered by sugacaney 2
·
0⤊
1⤋
Fish 1 = a
Fish 2 = b
Fish 3 = c
a = 2b
1/2a = c --> a = 2c
therefore c = b
and a = b + c
a + b + c = 64
a + a = 64
a = 32
b = 32/2 = 16
c = 16
First fish = 32oz, second and third fish 16oz each
2007-01-14 12:31:19
·
answer #6
·
answered by Tom :: Athier than Thou 6
·
0⤊
0⤋
The first fish is x, the second y and the third z.
x=2y
x=2z
Therefore y=z
x+y+z=64oz
2x=64oz
First fish is 32 oz (2 lbs)
Second fish is 16 oz (1 lb)
Third fish is also 16 oz (1lb)
2007-01-14 12:31:50
·
answer #7
·
answered by SteveT 7
·
0⤊
0⤋
the first=32,second=16,third=16
2007-01-14 12:29:27
·
answer #8
·
answered by bramo126 3
·
2⤊
0⤋
First - 32
Second - 16
Third - 16
Both the third and second are the same size. If the third is half of the size of first, that's the same as the first being twice as big as the third, which is what the second is.
The second and third both equal the same thing, so call them y. The first is x.
x = 2y
x + y + y = 64
4y = 64
y = 16
2007-01-14 12:31:03
·
answer #9
·
answered by marklemoore 6
·
0⤊
1⤋
1st fish is 2 times of 2nd fish
3rd fish is 0.5 times of 1st fish
therefore,
2nd fish is 1 times of 3rd fish
Ratio of Fish [1st : 2nd : 3rd] is [2 : 1: 1]
(FISH's weight = f)
2f + 1f + 1f = 64
4f = 64
f = 64 /4
= 16 ounces
Answer:
1st fish = 32 ounces
2nd fish = 16 ounces
3rd fish = 16 ounces
2007-01-14 12:55:21
·
answer #10
·
answered by wind_liao 2
·
0⤊
0⤋